Students' Creative Thinking Abilities in Solid Geometry Topics - Putri, Koriah Kartika; Khadijatuzzahra, Khansa (EDUPEDIA Publisher, 2025)
Creative thinking ability is an important ability for students and needed in future students. However, students’ creativity thinking ability in Indonesia is still low. This low ability is shown by the PISA results that put Indonesia in 63rd place. This study aims to analyze students’ creative thinking skills in the material solid figure. The subjects of this study were 33 grade IX junior high school students. This research is a qualitative descriptive study. The data collection technique in this study is a description of the techniques of creative thinking ability questions that represent each indicator of mathematical creative thinking skills. The results showed that overall mathematical creative thinking abilities of students were at a sufficient level. Based on gender, there are differences in students’ creative mathematical thinking skills, where female students’ abilities are better than male students’. In addition, their indicator are not yet well developed, namely elaboration.